Korelasi emosi dengan motivasi belajar siswa - Made Ani Ramadhani; Kasmawati Kasmawati; Itsnain Alfajri Husain (Universitas Indraprasta PGRI, 2023)
this study aims to determine how significant the relationship between emotions and learning motivation of fifth grade students at SD Negeri 4 Ranomeeto Barat. The research used is quantitative research using a survey approach method, namely a type of research where the independent variable is an event that has occurred. This research was conducted in Jati Bali Village, Ranomeeto Barat District, South Konawe Regency. The number of samples in this study were 20 students. Data collection techniques in this study using the questionnaire method. The data analysis technique used in this study is the normality test and linear correlation test. The results of the emotional questionnaire and student learning motivation were then analyzed to see if there was a significant relationship between emotion and student learning motivation. The results obtained in this study were that there was a significant relationship between emotions and learning motivation of fifth grade students at SD Negeri 4 Ranomeeto Barat.